For a peaceful transition in Sudan: Current developments and plausible scenarios - Annette Weber (Stiftung Wissenschaft und Politik (SWP), 2019)
There seems to be no end to the good news coming from the Horn of Africa. First, the Nobel peace prize for Ethiopia's young reformer Prime Minister Abiy Ahmed in October and then, in April, Sudan's dictator Omar al-Bashir was overthrown after thirty years of rule. After months of civil and peaceful protests, it was actually the Sudanese military that finally forced the ruler out of office. Then, less than four months later, military leaders and civilians led by Abdalla Hamdok, an economist with decades of experience at the United Nations, managed to form a government. Whether the transition continues to develop positively will depend on the willingness of the security apparatus to transfer power to civilian leaders. However, in stabilising the country and improving its economic performance much will depend on whether and to what extent external actors support Sudan's transformation process.
Keywords: 320